The impact of fiscal decentralization on accountability, economic freedom, and political and civil liberties in the Americas - Antonio N. Bojanic (Economies, 2018)
This paper analyzes the impact of fiscal decentralization on accountability, economic freedom, and political and civil liberties in the Americas. The findings indicate that decentralization initially hampers but eventually enhances accountability and political and civil liberties, in line with the hypothesized positive correlation between greater fiscal autonomy and a more inclusive, participatory government. The impact of fiscal decentralization on economic freedom, however, runs counter to expectations. Decentralization seems to initially bolster freedom, but it eventually constrains it, proving that greater accountability and political and civil liberties do not necessarily lead to greater economic freedom. When Canada and the US are excluded and the analysis is done with developing American nations only, the behavioral pattern regarding how fiscal decentralization affects the principal variables intensifies, noting that in developing countries the impact of fiscal decentralization is likely to be more consequential.
Keywords: E62; H70; O23; P52; 330; fiscal decentralization; economic freedom; political and civil liberties